Barriers to Political Analysis in Aid Bureaucracies: From Principle to Practice in DFID and the World Bank. (October 2015) - Yanguas, Pablo; Hulme, David
Highlights: Political-economy analysis (PEA) is yet to be institutionalized in aid agencies. We look at practice in two most likely cases: DFID and the World Bank. PEA and political engagement tend to be ad hoc and personality-dependent. Disbursement incentives and professional cultures remain key barriers. PEA needs a framing strategy that takes it beyond the governance silo. Summary: Politics has become a central concern in development discourse, and yet the use of political analysis as a means for greater aid effectiveness remains limited and contested within development agencies. This article uses qualitative data from two governance "leaders" – the United Kingdom Department for International Development and the World Bank – to analyze the administrative hurdles facing the institutionalization of political analysis in aid bureaucracies. We find that programing, management, and training practices across headquarters and country offices remain largely untouched by a political analysis agenda which suffers from its identification with a small cross-national network of governance professionals.